The contribution of the 240Ala:Glu:Glu:Thr243 sequence in the DE-loop of D2 to the acceptor side of Photosystem II - Ei Phyo Khaing; Tina C. Summerfield; Jack A. Forsman; Imre Vass; Priyanka Pradeep Patil; Julian J. Eaton-Rye (Photosynthesis Research, 2026)
The D2 protein of Photosystem II has five transmembrane helices (A-E). An extended loop, connecting helices D and E, contributes to the binding environments of the primary quinone electron acceptor Q A , and that of the bicarbonate bound to the non-heme iron between Q A and the secondary quinone electron acceptor Q B . The residues from Ala240 to Thr243 are within a conserved sequence ( 240 AEETYSMVTAN 250 ) that contributes to the stabilization of both Q A and bicarbonate. We have created the A240D, E241A, E242A, E242D and T243A mutants to study the role of these residues. The mutations in the A240D and E241A strains had little impact on PS II performance, except addition of formate altered chlorophyll a fluorescence decay in the E241A mutant following a single-turnover actinic flash. Measurements of variable chlorophyll a fluorescence and thermoluminescence showed the E242A and E242D mutants had impaired acceptor side electron transport consistent with a reduced redox gap between Q A and Q B . In addition, the T243A mutant exhibited a heightened susceptibility to photodamage. These data show that mutations introduced between 241 Glu–Thr 243 of D2 impair PS II activity but are less detrimental than mutations between the corresponding 243 Glu–Thr 245 residues of D1 in the vicinity of the Q B -binding site.

The contribution of D2-Arg265 to the molecular architecture of the quinone-Fe-bicarbonate acceptor complex of photosystem II - Victor Zhong; Imre Vass; Julian J. Eaton-Rye (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2026)

Arg24 and 26 of the D2 protein are important for photosystem II assembly and plastoquinol exchange in Synechocystis sp. PCC 6803 - Sandeep Biswas; Ei Phyo Khaing; Victor Zhong; Julian J. Eaton-Rye (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

International conference on “Photosynthesis and Hydrogen Energy Research for Sustainability-2023”: in honor of Robert Blankenship, Győző Garab, Michael Grätzel, Norman Hüner and Gunnar Öquist - Rajagopal Subramanyam; Tatsuya Tomo; Julian J. Eaton-Rye; Girayhan Yilmaz; Suleyman I. Allakhverdiev (Photosynthesis Research, 2024)

Indirect interactions involving the PsbM or PsbT subunits and the PsbO, PsbU and PsbV proteins stabilize assembly and activity of Photosystem II in Synechocystis sp. PCC 6803 - Faiza Arshad; Julian J. Eaton-Rye (Photosynthesis Research, 2024)
The low-molecular-weight PsbM and PsbT proteins of Photosystem II (PS II) are both located at the monomer-monomer interface of the mature PS II dimer. Since the extrinsic proteins are associated with the final step of assembly of an active PS II monomer and, in the case of PsbO, are known to impact the stability of the PS II dimer, we have investigated the potential cooperativity between the PsbM and PsbT subunits and the PsbO, PsbU and PsbV extrinsic proteins. Blue-native polyacrylamide electrophoresis and western blotting detected stable PS II monomers in the ∆PsbM:∆PsbO and ∆PsbT:∆PsbO mutants that retained sufficient oxygen-evolving activity to support reduced photoautotrophic growth. In contrast, the ∆PsbM:∆PsbU and ∆PsbT:∆PsbU mutants assembled dimeric PS II at levels comparable to wild type and supported photoautotrophic growth at rates similar to those obtained with the corresponding ∆PsbM and ∆PsbT cells. Removal of PsbV was more detrimental than removal of PsbO. Only limited levels of dimeric PS II were observed in the ∆PsbM:∆PsbV mutant and the overall reduced level of assembled PS II in this mutant resulted in diminished rates of photoautotrophic growth and PS II activity below those obtained in the ∆PsbM:∆PsbO and ∆PsbT:∆PsbO strains. In addition, the ∆PsbT:∆PsbV mutant did not assemble active PS II centers although inactive monomers could be detected. The inability of the ∆PsbT:∆PsbV mutant to grow photoautotrophically, or to evolve oxygen, suggested a stable oxygen-evolving complex could not assemble in this mutant.

Preface to the special issue: the keynote lectures of the 18th International Congress on Photosynthesis Research - Terry M. Bricker; Julian J. Eaton-Rye (Photosynthesis Research, 2023)

Correction to: Govindjee’s 90th birthday: a life dedicated to photosynthesis - Alexandrina Stirbet; Dmitry Shevela; Ashwani Pareek; Sushma Naithani; Lars Olof Björn; Julian J. Eaton-Rye; Arthur Nonomura (Plant Physiology Reports, 2022)

Govindjee’s 90th birthday: a life dedicated to photosynthesis - Alexandrina Stirbet; Dmitry Shevela; Ashwani Pareek; Sushma Naithani; Lars Olof Björn; Julian J. Eaton-Rye; Arthur Nonomura (Plant Physiology Reports, 2022)

The PsbJ protein is required for photosystem II activity in centers lacking the PsbO and PsbV lumenal subunits - Priscilla Choo; Jack A. Forsman; Liangliang Hui; Ei Phyo Khaing; Tina C. Summerfield; Julian J. Eaton-Rye (Photosynthesis Research, 2022)

International conference on “Photosynthesis and Hydrogen Energy Research for Sustainability-2019”: in honor of Tingyun Kuang, Anthony Larkum, Cesare Marchetti, and Kimiyuki Satoh - Maria M. Borisova-Mubarakshina; Anatoly A. Tsygankov; Tatsuya Tomo; Suleyman I. Allakhverdiev; Julian J. Eaton-Rye; Govindjee Govindjee (Photosynthesis Research, 2020)

The PsbT protein modifies the bicarbonate-binding environment of Photosystem II - Jack A. Forsman; Robert D. Fagerlund; Sandeep Biswas; Tina C. Summerfield; Julian J. Eaton-Rye (New Zealand Journal of Botany, 2020)

Celebrating the contributions of Govindjee after his retirement: 1999–2020 - Alexandrina Stirbet; Lars Olof Björn; Dmitry Shevela; Suleyman I. Allakhverdiev; Arthur Nonomura; Xin-Guang Zhu; Dušan Lazár; Ashwani Pareek; Győző Garab; Julian J. Eaton-Rye (New Zealand Journal of Botany, 2020)

An updated system for the targeted mutagenesis of the psbDI:psbC operon in Synechocystis sp. PCC 6803: mutations targeting Asp460 in CP43 of Photosystem II reduce oxygen-evolving activity and perturb electron transfer in the quinone-Fe-acceptor complex - Ei Phyo Khaing; Victor Zhong; Julian J. Eaton-Rye (New Zealand Journal of Botany, 2020)

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: part 2 - Julian J. Eaton-Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2020)

The diversity and distribution of D1 proteins in cyanobacteria - Kevin J. Sheridan; Elizabeth J. Duncan; Julian J. Eaton-Rye; Tina C. Summerfield (Photosynthesis Research, 2020)

An improved system for the targeted mutagenesis of the psbA2 gene in Synechocystis sp. PCC 6803: mutation of D1‐Glu244 to His impairs electron transfer between Q A and Q B of Photosystem II - Jack A. Forsman; Regan T. Winter; Julian J. Eaton‐Rye (New Zealand Journal of Botany, 2019)
The cyanobacterium Synechocystis sp. PCC 6803 has three copies of the psbA gene encoding the D1 reaction centre protein of Photosystem II (PS II). We have designed a mutagenesis system that allows introduction of mutations into the constitutively expressed psbA2 copy without affecting the expression of any flanking genes. A triple deletion strain was constructed in which psbA1 and psbA3 were removed by markerless deletions and psbA2 was replaced by a chloramphenicol‐resistance cassette. A vector was then designed to enable the reintroduction of psbA2 in the chromosome using a kanamycin‐resistance cassette as a selectable marker. This system was used to generate a control strain, which had an unmodified copy of psbA2 , and two mutant strains which contained a copy of psbA2 where the codon for D1‐Glu244 had been mutated to code for a His or Asp. The D1‐Glu244 residue was targeted as it has been hypothesised to participate in a hydrogen‐bond network that is required for protonation of the PS II secondary plastoquinone electron acceptor Q B . While the phenotype of the control strain was similar to wild type, the E244H mutant exhibited impaired oxygen evolution and altered electron transfer between the primary quinone acceptor Q A and Q B . However, substitution of Glu‐244 by Asp resulted in a mutant more closely resembling the control strain.

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: Part 1 - Julian J. Eaton‐Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2019)

Govindjee: a lifetime in photosynthesis - Julian J. Eaton-Rye (Photosynthesis Research, 2019)

Introduction: proceedings of the 2015 New Zealand symposium on algae and photosynthetic prokaryotes - Michael A. Packer; Julian J. Eaton‐Rye; Tina C. Summerfield; Benoit Guieysse; Susanna A. Wood (New Zealand Journal of Botany, 2017)

Modular growth vessels for the cultivation of the cyanobacterium Synechococcus sp. PCC 7002 - Simon A. Jackson; Julian J. Eaton‐Rye (New Zealand Journal of Botany, 2017)
Synechococcus sp. PCC 7002 is a euryhaline cyanobacterium that serves as a model organism for studies of photosynthesis and cellular metabolism. At high light intensity Synechococcus sp. PCC 7002 exhibits a fast growth rate and rapid biomass accumulation, making it an ideal candidate for the production of biofuels and commercially valuable secondary metabolites. To fully realise the production potential for this cyanobacterium a system is required to maintain axenic cultures under optimal growth conditions. We have designed and constructed two sizes of modular culture vessel systems, designed specifically to meet the abnormally high light penetration requirements of Synechococcus sp. PCC 7002. The smaller volume culture vessels are best suited to phenotype analysis, allowing multiple candidate strains to be screened simultaneously, whereas the larger vessels are designed to facilitate higher biomass production.

Characterization of a Synechocystis sp. PCC 6803 double mutant lacking the CyanoP and Ycf48 proteins of Photosystem II - Simon A. Jackson; Julian J. Eaton-Rye (Photosynthesis Research, 2015)

Algal and cyanobacterial bioenergy and diversity - Julian J. Eaton‐Rye; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2014)

Mutational analysis of the stability of Psb27 from Synechocystis sp. PCC 6803: implications for models of Psb27 structure and binding to CP43 - Peter D. Mabbitt; Julian J. Eaton-Rye; Sigurd M. Wilbanks (European Biophysics Journal, 2013)

Gold or silver deposited on layered manganese oxide: a functional model for the water-oxidizing complex in photosystem II - Mohammad Mahdi Najafpour; Fahimeh Rahimi; Davood Jafarian Sedigh; Robert Carpentier; Julian J. Eaton-Rye; Jian-Ren Shen; Suleyman I. Allakhverdiev (Photosynthesis Research, 2013)

Imidazolium or guanidinium/layered manganese (III, IV) oxide hybrid as a promising structural model for the water-oxidizing complex of Photosystem II for artificial photosynthetic systems - Mohammad Mahdi Najafpour; Mahmoud Amouzadeh Tabrizi; Behzad Haghighi; Julian J. Eaton-Rye; Robert Carpentier; Suleyman I. Allakhverdiev (Photosynthesis Research, 2013)

Govindjee at 80: more than 50 years of free energy for photosynthesis - Julian J. Eaton-Rye (Photosynthesis Research, 2013)

A Cost-Effective Solution for the Reliable Determination of Cell Numbers of Microorganisms in Liquid Culture - Jacob J. Lamb; Julian J. Eaton-Rye; Martin F. Hohmann-Marriott (Current Microbiology, 2013)

Biological water-oxidizing complex: a nano-sized manganese–calcium oxide in a protein environment - Mohammad Mahdi Najafpour; Atefeh Nemati Moghaddam; Young Nam Yang; Eva-Mari Aro; Robert Carpentier; Julian J. Eaton-Rye; Choon-Hwan Lee; Suleyman I. Allakhverdiev (Photosynthesis Research, 2012)

An LED-based fluorometer for chlorophyll quantification in the laboratory and in the field - Jacob J. Lamb; Julian J. Eaton-Rye; Martin F. Hohmann-Marriott (Photosynthesis Research, 2012)

Directed mutagenesis of the transmembrane domain of the PsbL subunit of photosystem II in Synechocystis sp. PCC 6803 - Hao Luo; Julian J. Eaton-Rye (Photosynthesis Research, 2008)

Snapshots of the Govindjee lab from the late 1960s to the late 1990s, and beyond… - Julian J. Eaton-Rye (Photosynthesis Research, 2007)

Global gene expression of a ΔPsbO:ΔPsbU mutant and a spontaneous revertant in the cyanobacterium Synechocystis sp. strain PCC 6803 - Tina C. Summerfield; Julian J. Eaton-Rye; Louis A. Sherman (Photosynthesis Research, 2007)

Phosphate sensing in Synechocystis sp. PCC 6803: SphU and the SphS–SphR two-component regulatory system - Waraporn Juntarajumnong; Tripty A. Hirani; Joanne M. Simpson; Aran Incharoensakdi; Julian J. Eaton-Rye (Archives of Microbiology, 2007)

Celebrating Govindjee’s 50 years in photosynthesis research and his 75th birthday - Julian J. Eaton-Rye (Photosynthesis Research, 2007)

Identification of the Start Codon for sphS Encoding the Phosphate-Sensing Histidine Kinase in Synechocystis sp. PCC 6803 - Waraporn Juntarajumnong; Aran Incharoensakdi; Julian J. Eaton-Rye (Current Microbiology, 2007)

Requirements for different combinations of the extrinsic proteins in specific cyanobacterial Photosystem II mutants - Julian J. Eaton-Rye (Photosynthesis Research, 2005)

Investigation of a requirement for the PsbP-like protein in Synechocystis sp. PCC 6803 - Tina C. Summerfield; Regan T. Winter; Julian J. Eaton-Rye (Photosynthesis Research, 2005)

Amino acid deletions in the cytosolic domains of the chlorophyll a-binding protein CP47 slow QA − oxidation and/or prevent the assembly of Photosystem II - Shannon M. Clarke; Christiane Funk; Garth S. Hendry; Jackie A. Shand; Tom Wydrzynski; Julian J. Eaton-Rye (Plant Molecular Biology, 2002)

Characterization of a two-component signal transduction system involved in the induction of alkaline phosphatase under phosphate-limiting conditions in Synechocystis sp. PCC 6803 - Tripty A. Hirani; Iwane Suzuki; Norio Murata; Hidenori Hayashi; Julian J. Eaton-Rye (Plant Molecular Biology, 2001)

Amino acid deletions in loop C of the chlorophyll a-binding protein CP47 alter the chloride requirement and/or prevent the assembly of photosystem II - Shannon M. Clarke; Julian J. Eaton-Rye (Plant Molecular Biology, 2000)